“A Little Bit out of Control”: Doing Identity-Work by Chinese University Teachers in Online Teachings (Sinología hispánica. China Studies Review, 2020)
Online classrooms have offered “unique and irreplaceable” sites for teachers to doidentity work. In this article, we aim to explore what and how different types of teacher identities areconstructed and negotiated in online teachings. We draw on 6h of video-recorded online instructionsdelivered by four teachers from the Department of Foreign Studies in China’s local university. Dataanalysis finds Chinese university teachers in online lessons mainly construct three types of identities:professional identity, affective identity, and technical identity. Professional identity is related toteachers’ epistemic and deontic authority. Affective identity is reflected in the way teachers negotiateinterpersonal relationships with students. Technical identity is made salient when teachers mention thetechnological environment or (in)ability. These identities are constructed through different discursivepractices, such as person-referencing practices and speech acts. This study also yields interestingfindings on the interlinks and struggles of teacher identities in an online pedagogical environment. Wehope that it could provide some insights for the current teacher training and education in China.